2006
DOI: 10.5194/angeo-24-173-2006
|View full text |Cite
|
Sign up to set email alerts
|

The F-region trough: seasonal morphology and relation to interplanetary magnetic field

Abstract: Abstract. We present here the results of a statistical study of the ionospheric trough observed in 2003 by means of satellite tomography. We focus on the seasonal morphology of the trough occurrence and investigate the trough latitude, width and the horizontal gradients at the edges, at different magnetic local times, as well as their relations to geomagnetic activity and the interplanetary magnetic field. A seasonal effect is noticed in the diurnal variation of the trough latitude, indicating that summer clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
33
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 19 publications
11
33
0
Order By: Relevance
“…In fact Werner and Prolss (1997) found that troughs during noontime are located at high latitudes, during the afternoon they migrate toward lower latitudes, reaching the minimum early in the morning and showing an asymmetry of the trough position around noon. This explanation is confirmed by the correspondence with the reconstruction of the equatorward and poleward walls of the troughs during 2003 by Voiculescu et al (2006). In a recent paper Wielgosz and co-authors (2004) demonstrate that the TEC distribution follows the position of the troughs, indicating the presence of large gradients in the electron concentration.…”
Section: Phase Scintillationsupporting
confidence: 55%
“…In fact Werner and Prolss (1997) found that troughs during noontime are located at high latitudes, during the afternoon they migrate toward lower latitudes, reaching the minimum early in the morning and showing an asymmetry of the trough position around noon. This explanation is confirmed by the correspondence with the reconstruction of the equatorward and poleward walls of the troughs during 2003 by Voiculescu et al (2006). In a recent paper Wielgosz and co-authors (2004) demonstrate that the TEC distribution follows the position of the troughs, indicating the presence of large gradients in the electron concentration.…”
Section: Phase Scintillationsupporting
confidence: 55%
“…In the past decades, various ground‐ and space‐based techniques were employed in numerous MIT investigations, so the general morphology and occurrence probability are reasonably well known [ Moffett and Quegan , 1983; Rodger et al , 1992; Scali , 1992]. Globally, the MIT occurs primarily in darkness; thus is observed most regularly in winter (November, December, January, and February for the Northern Hemisphere and May, June, July, and August for the Southern Hemisphere) and equinox; in summer it is restricted mainly to the midnight sector [e.g., Rodger et al , 1992; Voiculescu et al , 2006]. Locally, higher incidences at daytime than nighttime was also reported [ Mallis and Essex , 1993].…”
Section: Introductionmentioning
confidence: 99%
“…Local time also affects the MIT location. It moves equatorward with local time in the evening sector, reaches its lowest latitude around midnight and returns to higher latitudes before dawn [ Evans , 1977; Whalen , 1989; Werner and Prölss , 1997; Voiculescu et al , 2006]. Numerous publications on the MIT climatology have been reviewed for times [ Evans , 1977; Spiro , 1978; Prölss , 2007; Rodger , 2008; Krankowski et al , 2009], so MIT's relationships to season, local time and geomagnetic activity are well established.…”
Section: Introductionmentioning
confidence: 99%
“…Satellite tomography allows the observation of the F-region within a wide latitudinal range and it seems to be very suitable for the trough studies Pryse et al, 1998;Mitchell et al, 1997;Voiculescu et al, 2006). However the phase method used in these publications bears serious methodological limitations and such results should be used with care.…”
Section: Introductionmentioning
confidence: 96%
“…EISCAT observations can provide the required information on the electron density distribution in the trough area and this possibility has been used by researchers (Jones et al, 1997; Voiculescu et al, 2006). Using common program (CP1 and CP2) field-aligned observations (a description of various EISCAT Programs may be found in EISCAT, 1991, also in Collis, 1995 we watch the trough passage in time rather than in space as in the case of CP3 or satellite observations.…”
Section: Introductionmentioning
confidence: 98%